Pemanfaatan Platform Youtube “Gadgetin” sebagai New Media Pencarian Informasi Teknologi - Dandi Perdana Putra; Solihah Titin Sumanti; Faisal Riza (IAI Nasional Laa Roiba Bogor, 2025)
This study aims to understand the nature of the phenomenon of the YouTube GadgetIn audience, using an illustrative subjective methodology involving a top-down encounter strategy. The researchers applied an observational information gathering procedure to examine perceptions of the content presented by YouTube GadgetIn, especially related to meeting the needs of viewers in the world of technology. This study also explores views on YouTube as a social media using New Media and Uses & Gratifications theories, to see how media can evolve and develop by utilizing ideas from pre-existing media. The results of this study are expected to provide new insights into audience interaction with technology content and the role of YouTube in the context of social media.